A Case-control Study in Hiroshima and Nagasaki Examining Non-radiation Risk Factors for Thyroid Cancer - Nagano, Jun; Mabuchi, Kiyohiko; Yoshimoto, Yasuhiko; Hayashi, Yuzo; Tsuda, Nobuo; Land, Charles; Kodama, Kazunori (Journal of epidemiology, 2007)
Because little is known about the etiology of thyroid cancer in Japan, we conducted a case-control study of thyroid cancer and lifestyle and other risk factors. The present report focuses on medical history, family history, smoking and alcohol drinking, and their interactions with radiation exposure. Thyroid cancer cases reported to the Hiroshima and Nagasaki tumor registries during 1970-1986 were histologically reviewed by pathologists. For each of 362 cases with papillary or follicular adenocarcinoma diagnosed at <75 years of age, one control without cancer matched on city, sex, year of birth, and atomic-bomb radiation exposure was selected from the Life Span Study cohort or the offspring cohort. The cohort subjects were residents of Hiroshima and Nagasaki with or without atomic-bomb radiation exposure. Information on risk factors was obtained through a pre-structured interview carried out in 1986-1988. Analysis using conditional logistic regression showed history of goiter or thyroid nodule and family history of cancer to be significantly associated with an increased odds ratio for thyroid cancer. Smoking and alcohol drinking were significantly and independently associated with a reduced odds ratio. Interaction between smoking and alcohol drinking was not evident based on either an additive model or a multiplicative model. Radiation exposure did not significantly modify the associations between these factors and thyroid cancer risk. History of goiter/nodule and family history of cancer were risk factors for thyroid cancer. Smoking and alcohol drinking were independently associated with reduced risk. Self-reported retrospective information presents some limitations in interpretation of the data.